Management of drug-induced liver injury associated with anti-cancer therapy - Vincenzi, Bruno; Yimin, Mao; Andrade, Raúl J.; Morales Castillo, Mauricio; Akhundova-Unadkat, Gamar; Mato, José M. (Frontiers in Physiology, 2025)
Drug-induced liver injury (DILI) is a leading cause of drug withdrawal, a particular cause for concern among patients receiving anti-cancer treatment. This review summarizes the available evidence on the efficacy of hepatoprotective drugs in normalizing liver enzyme abnormalities among patients with DILI due to treatment with anti-cancer therapies. Across relevant publications, the effects of several compounds on anti-cancer therapy-induced DILI were assessed. Treatment with hepatoprotective agents which is usually initiated after DILI has been detected and involves cessation of causative anti-cancer therapy, has demonstrated improvements in liver enzyme elevation. However, prophylactic treatment with two agents in particular, ademetionine and bicyclol have shown hepatoprotective effects that enabled patients to continue with their anti-cancer therapy with a reduced subsequently reduced risk of hepatotoxicity. While these publications show some evidence for the benefits of hepatoprotective agents among patients with DILI due to anti-cancer therapy, more research is needed to fully determine the effects of hepatoprotective drugs in resolving DILI signs and symptoms among patients receiving treatment for cancer.